2011
DOI: 10.1007/s00737-010-0202-2
|View full text |Cite
|
Sign up to set email alerts
|

The premenstrual symptoms screening tool revised for adolescents (PSST-A): prevalence of severe PMS and premenstrual dysphoric disorder in adolescents

Abstract: The Premenstrual Symptoms Screening Tool was modified for use in adolescents and piloted in 578 girls at three international sites. Nearly one third (29.6%) reported experiencing severe PMS or PMDD, with irritability being the most commonly reported symptom. Rates of menstrual-related pain were high, particularly in those with severe PMS or PMDD. Severe PMS and PMDD present with similar rates and symptoms in adolescents as in adults, and the Premenstrual Symptoms Screening Tool modified for adolescents is a fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
110
2
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(133 citation statements)
references
References 9 publications
15
110
2
6
Order By: Relevance
“…This finding not supported by Nageebfinding, (24)who found no significant relationship between menstrualinterval and severity of PMS (p= 0.242).This controversy might be other factors such as environment, food habits or obstetrical disease. Regarding to dysmenorrhea, the current study found more than half of the study sample (n=121)had severdysmenorrhea, which was significantly related with severe premenstrual symptoms and higher scores on visual analogue scale.These findings agree with study by Steiner, (25)who reported that the prevalence of dysmenorrhea was high, particularly in those with severe PMS or PMDDas 63.7% from the study sample suffer from no/mild PMS, 81.7% experience severe PMS.Although some studies have reported no relation between dysmenorrhea and PMS (17,26). The rational for this finding due to the Biochemical changes in severe PMS and dysmenorrhea may correspond with each other, and reduced prostaglandin levels may relieve both of them.…”
Section: Reproductive Predictorssupporting
confidence: 94%
“…This finding not supported by Nageebfinding, (24)who found no significant relationship between menstrualinterval and severity of PMS (p= 0.242).This controversy might be other factors such as environment, food habits or obstetrical disease. Regarding to dysmenorrhea, the current study found more than half of the study sample (n=121)had severdysmenorrhea, which was significantly related with severe premenstrual symptoms and higher scores on visual analogue scale.These findings agree with study by Steiner, (25)who reported that the prevalence of dysmenorrhea was high, particularly in those with severe PMS or PMDDas 63.7% from the study sample suffer from no/mild PMS, 81.7% experience severe PMS.Although some studies have reported no relation between dysmenorrhea and PMS (17,26). The rational for this finding due to the Biochemical changes in severe PMS and dysmenorrhea may correspond with each other, and reduced prostaglandin levels may relieve both of them.…”
Section: Reproductive Predictorssupporting
confidence: 94%
“…Therefore, during the last 2 decades; several studies have been conducted on various treatment options regarding PMS [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Ayrıca örneklemimiz birçok çalışmaya göre AÖDS oranın yüksek olduğu yaş grubuna sahip bir popülasyondan oluşmak-tadır [5,17]. Daha genç kadınların bulunduğu bazı çalışmalarda AÖDS %8'in üstünde bir oranda bildirilmiştir [19]. Yine aynı ça-lışmada Amerika Birleşik Devletleri ve Kanada'da 12-18 yaş arası ergen kadınlarda benzer ölçme aracıyla bulunan AÖDS oranı %10'un üzerindedir [19].…”
Section: Discussionunclassified
“…Bahse konu geçerlilik çalış-masında AÖDB oranı %5,1, orta-şiddetli PMS/AÖS % 20,7, hafif PMS/AÖS ya da belirtisiz grup %65 olarak bulunmuştur. PSST gereciyle ergenlerde yapılan bir başka çalışmada da erişkinler-dekine benzer oranlar bulunmuş, PSST ergenlerde premenstrü-el belirtileri taramak için hızlı ve güvenilir bir gereç olarak değerlendirilmiştir [19]. Yine bu gereçle Buttner ve arkadaşlarının (2013) yaptığı bir çalışmada PMS/AÖS/AÖDB doğum-sonrası depresyonda bir risk faktörü olarak bulunmuştur [20].…”
Section: Introductionunclassified